The genome and genetics of a high oxidative stress tolerant Serratia sp. LCN16 isolated from the plant parasitic nematode Bursaphelenchus xylophilus. (December 2016) - Vicente, Claudia; Nascimento, Francisco; Ikuyo, Yoriko; Cock, Peter; Mota, Manuel; Hasegawa, Koichi
Abstract Background Pine wilt disease (PWD) is a worldwide threat to pine forests, and is caused by the pine wood nematode (PWN)Bursaphelenchus xylophilus . Bacteria are known to be associated with PWN and may have an important role in PWD.Serratia sp. LCN16 is a PWN-associated bacterium, highly resistant to oxidative stress in vitro, and which beneficially contributes to the PWN survival under these conditions. Oxidative stress is generated as a part of the basal defense mechanism used by plants to combat pathogenic invasion. Here, we studied the biology ofSerratia sp. LCN16 through genome analyses, and further investigated, using reverse genetics, the role of two genes directly involved in the neutralization of H2 O2, namely the H2 O2 transcriptional factoroxyR ; and the H2 O2 -targeting enzyme, catalasekatA . Results Serratia sp. LCN16 is phylogenetically most closely related to the phytosphere group ofSerratia, which includesS. proteamaculans, S. grimessi andS. liquefaciens . Likewise, Serratia sp. LCN16 shares many features with endophytes (plant-associated bacteria), such as genes coding for plant polymer degrading enzymes, iron uptake/transport, siderophore and phytohormone synthesis, aromatic compound degradation and detoxification enzymes. OxyR and KatA are directly involved in the high tolerance to H2 O2 ofSerratia sp. LCN16. Under oxidative stress, Serratia sp. LCN16 expresseskatA independently of OxyR in contrast withkatG which is under positive regulation of OxyR.Serratia sp. LCN16 mutants foroxyR (oxyR ::int(614)) andkatA (katA ::int(808)) were sensitive to H2 O2 in relation with wild-type, and both failed to protect the PWN from H2 O2 -stress exposure. Moreover, both mutants showed different phenotypes in terms of biofilm production and swimming/swarming behaviors. Conclusions This study provides new insights into the biology of PWN-associated bacteriaSerratia sp. LCN16 and its extreme resistance to oxidative stress conditions, encouraging further research on the potential role of this bacterium in interaction with PWNin planta environment.